The nexus between tourism development and economic growth in Eastern Indonesia: a panel VECM approach - Amaluddin Amaluddin (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
The empirical nexus between tourism development and economic growth have been widely examined, however, the empirical results generally produce diverse conclusion and often debated. The purpose of this empirical study is, firstly, to investigate and analyze the dynamic relationship between tourism sector development and economic growth both in the short and long run. Secondly, to examine the direction of causality between tourism development and economic growth in Eastern Indonesia over the period 2010-2017. This study employed a panel vector error correction model (PVECM) for the quantitative analysis approach from panel data of 12 provinces in eastern Indonesia. The empirical findings of this study were: 1) In the long run, the relationship between tourism development and economic growth supported the feedback causality hypothesis where changes and expansion in the tourism development affect economic growth and increasing economic growth have an impact on the expansion of the tourism sector (bi-directional causality). 2) The empirical findings corroborated the growth-led tourism hypothesis in the short run which argues that the achievements of economic growth affect the expansion of tourism development. In the short run, this empirical study only found a one-way causality running from economic growth to tourism development.